Enhancing lentiviral transduction to generate melanoma-specific human T cells for cancer immunotherapy - Simon, Bianca; Harrer, Dennis C.; Thirion, Christian; Schuler-Thurner, Beatrice; Schuler, Gerold; Uslu, Ugur (Journal of Immunological Methods, 2019)
Introduction of a tumor antigen-specific T cell receptor (TCR) into patient-derived lymphocytes has already exhibited promising results for the treatment of melanoma and other malignancies in clinical trials. However, insufficient or unsuccessful ex vivo manufacturing of engineered T cells due to low expansion and/or transduction rate can still be observed in some patients. Thus, we isolated human CD8+ T cells from healthy donors and equipped them with a gp100-specific TCR using a lentiviral construct in combination with a novel chemical lentiviral transduction enhancer (Lentiboost) to increase the rate of transduced cells. Following experiments to determine the ideal multiplicity of infection (MOI) and to analyze the efficacy of the transduction enhancer using a GFP-encoding lentivirus, we analyzed in the next step the transduction rate, cell count, and functionality of gp100 TCR-transduced T cells, i.e. antigen-specific cytokine secretion and lytic capacity. In order to increase the number of transduced cells, antigen-specific stimulation was performed, either once for 1 week (1st activation) or twice for another week (2nd activation). In general, each cycle of antigen-specific stimulation resulted in expansion of TCR-positive cells, while no further significant increase of transduced cells was observed after 2nd activation. Cytokine production pattern of transduced cells after antigen encounter, however, revealed significant antigen-specific secretion of TNF and IFNγ after the 1st as well as the 2nd activation. Furthermore, TCR T cells, either activated once or twice, showed significant cytotoxicity towards antigen-positive tumor cells. Taken together, these results show that it is feasible to transduce human T cells using a lentiviral construct in combination with this novel lentiviral transduction enhancer, which shows potential in the growing field of cancer immunotherapy.
CRIS-Team Scopus Importer:2019-06-25
Keywords: Adoptive T cell therapy; gp100; Lentiboost; Lentivirus; T cell receptor; Tumor antigen